TEKNIK KOLEKSI DAN PRESERVASI TUMBUHAN Nephrolepis biserrata (Paku) DI KELURAHAN TURIDA, KECAMATAN SANDUBAYA, KOTA MATARAM - Oktavita Wulandari; Sulistia Febriani; Muhammad Zulhimi; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Nephrolepis biserrata is a species of fern commonly found in tropical environments with high humidity. This plant plays an ecological role in maintaining environmental humidity and increasing vegetation diversity. This study aims to determine the collection and preservation techniques for Nephrolepis biserrata plants found in Turida Village, Sandubaya District, Mataram City. The research method used was direct field observation through exploration and sampling. Samples were identified based on morphological characteristics, including roots, stems, and leaves. Preservation techniques were carried out using herbarium methods, including cleaning, pressing, drying, labeling, and storing the specimens. The results showed that Nephrolepis biserrata was found growing on damp and shady walls. The collected samples were still small, so they did not yet show sori on the undersides of the leaves. Proper collection and preservation techniques are important to maintain the quality of the specimens as learning and research materials.